Ego-Resiliency and physically-disabled learners: The Implementation of a Multiple Intelligences Teaching Approach - Nayyereh Ghaznavi; Mehry Haddad Narafshan; Massoud Tajadini (Tabriz University of Medical Sciences, 2021)
Background: Gardner's multiple intelligences (MI) theory offers great opportunities to improve the diverse abilities potential in disabled learners. The current study investigated the effect of the MI teaching approach on physically disabled learners' MI and ego resiliency. Methods: The purposive sample included male and female participants aged 14 to 30 years at the Arseye-Talash Institute in Urmia, West Azerbaijan for students with disabilities. To gain a complete picture of the phenomenon, the study used self-report questionnaires and semi-structured interviews. The study utilized an experimental design that included 30 participants overall, with 10 participants in a control group and 20 participants in two experimental groups according to the multiple intelligences-based instructions (MIBI) they received: first language (Persian)-oriented MIBIs & second language (English)-oriented MIBIs. For both experimental groups (n = 20), active and passive intelligences of the students were identified using a MI test. Then, the instruction was tailored to designing tasks to activate the passive intelligence for both groups. The control group (n = 10) received no training. The data were analyzed in SPSS software using ANOVA and Tukey's post hoc HSD test. Results: Findings indicated that the use of the MI-based teaching approach contributed to a significant improvement in the learners' MI (P <0.01) and ego resiliency (P <0.01). Furthermore, findings showed a positive impact of L2-oriented (English) MIBIs compared with L1-oriented (Persian) MIBI on physically disabled learners' ego resiliency (P <0.01); however, no significant difference was found between the two languages' MIBIs (P >0.01). Conclusion: The more diverse a learner's experience, the more effective their learning will be, and accordingly, the more successful they will be in a world of challenges. This holds especially true for physically disabled learners who have diverse experiences and hence diverse learning needs.